Methodological Model for Developing Communicative Competence of Medical University Students Based on Interactive Methods using Authentic Fictional Video Materials (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Objective: To develop and test a methodological model for improving the English communicative competence of medical university students using authentic artistic films.Material and Methods: The study used authentic video materials, specifically the medical TV series "House M.D.," along with a specially developed educational guide. Interactive teaching methods were applied to develop the four components of communicative competence. The study involved conducting classes using these materials and methods, as well as testing to evaluate their effectiveness.Results: The use of authentic artistic films in the learning process significantly improved students' communicative competence. According to the study, the experimental groups showed substantial improvement in material retention compared to the control groups: 62% of students mastered all four aspects (compared to 1.1% in the control group), 34.5% mastered three aspects (compared to 2.3%), 40.7% mastered two aspects (compared to 20.9%), and only 2.8% of the experimental group did not master any aspects (compared to 45.8% in the control group). The only negative result in mastering one aspect (15.8% compared to 29.9%) is still considered positive since most students in the experimental group mastered more aspects and provided their responses. The experiment demonstrated high results in forming discursive, sociolinguistic, and strategic competencies, as well as the ability to adequately choose and use language tools in various situations.Conclusion: The methodological model based on the use of authentic artistic films and interactive teaching methods proved effective in improving the English communicative competence of medical university students. The study results confirm the feasibility of applying this model to achieve high educational goals.